The Motivation Behind CSR Manager Role in Indonesian Mining Companies - Zainal, Rabin Ibnu; Fitriya, Fitriya; Santoso, Teguh Iman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 1 (2022), 2022)
The goal of this research is to investigate the underlying motivations for the role of the CSR manager. The study used smart PLS analysis to identify three motivations behind the role of CSR managers in mining companies, namely economic, legal and ethical domains. The study includes 114 managers or representatives from CSR-implementing mining companies in South Sumatera, Indonesia. The manager of mining companies in this region is mandated to implement CSR based on the rules of legislation.  The study found that following Indonesian CSR legislation is not a significant motivation for CSR managers. Instead, CSR managers' decisions are influenced by economic motivation. Furthermore, analysis results revealed that CSR managers' motivation for economic and legal domains influenced their role in CSR. Keywords:  CSR, mining companies, motivation, role.